The RelB alternative NF-kappaB subunit promotes autophagy in 22Rv1 prostate cancer cells in vitro and affects mouse xenograft tumor growth in vivo - Labouba, Ingrid (Cancer Cell Int, 2014)
BACKGROUND: The involvement of NF-κB signaling in prostate cancer (PCa) has largely been established through the study of the classical p65 subunit. Nuclear localization of p65 in PCa patient tissues has been shown to correlate with biochemical recurrence, while in vitro studies have demonstrated that the classical NF-κB signaling pathway promotes PCa progression and metastatic potential. More recently, the nuclear location of RelB, a member of the alternative NF-κB signaling, has also been shown to correlate with the Gleason score. The current study aims to clarify the role of alternative NF-κB in PCa cells by exploring, in vitro and in vivo, the effects of RelB overexpression on PCa biology. METHODS: Using a lentivirus-expression system, we constitutively overexpressed RelB or control GFP into 22Rv1 cells and monitored alternative transcriptional NF-κB activity. In vivo, tumor growth was assessed after the injection of 22Rv1-derived cells into SCID mice. In vitro, the impact of RelB on 22Rv1 cell proliferation was evaluated in monolayer culture. The anchorage-independent cell growth of derived-22Rv1 cells was assessed by soft agar assay. Apoptosis and autophagy were evaluated by Western blot analysis in 22Rv1-derived cells cultured in suspension using poly-HEMA pre-coated dishes. RESULTS: The overexpression of RelB in 22Rv1 cells induced the constitutive activation of the alternative NF-κB pathway. In vivo, RelB expression caused a lag in the initiation of 22Rv1-induced tumors in SCID mice. In vitro, RelB stimulated the proliferation of 22Rv1 cells and reduced their ability to grow in soft agar. These observations may be reconciled by our findings that, when cultured in suspension on poly-HEMA pre-coated dishes, 22Rv1 cells expressing RelB were more susceptible to cell death, and more specifically to autophagy controlled death. CONCLUSIONS: This study highlights a role of the alternative NF-κB pathway in proliferation and the controlled autophagy. Thus, the interplay of these properties may contribute to tumor survival in stress conditions while promoting PCa cells growth contributing to the overall tumorigenicity of these cells.